The Influence of Capital Structure, Financial Performance, Growth and Company Size on The Value of Manufacturing Companies Listed on The Indonesia Stock Exchange - Sinurat, Mangasi; Ilham, Rico Nur (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2023)
The research method used is the method of qualitative data and quantitative data. While the data used is primary data. 1) a table value of 2,026 is obtained. From this description it can be seen that tcount (0.088) < ttable (2.026), likewise with a significant value of 0.931 > 0.05, it can be concluded that the first hypothesis is rejected, meaning that the Capital Structure variable (X1) has no significant effect to the variable Firm Value (Y). 2) a table value of 2,026 is obtained. From this description it can be seen that tcount (3.354) > ttable (2.026), likewise with a significant value of 0.002 <0.05, it can be concluded that the second hypothesis is accepted, meaning that the Financial Performance variable (X2) has a significant effect to the variable Firm Value (Y). a table value of 2,026 is obtained. From this description it can be seen that tcount (0.358) < ttable (2.026), likewise with a significant value of 0.723 > 0.05, it can be concluded that the third hypothesis is rejected, meaning that the company growth variable (X3) has a significant effect on the variable Firm Value (Y). 3) a table value of 2,026 is obtained. From this description it can be seen that tcount (0.060) < ttable (2.026), likewise with a significance value of 0.953 > 0.05, it can be concluded that the fourth hypothesis is rejected, meaning that the variable Firm Size (X4) has a significant effect to the variable Firm Value (Y). 4) Ftable value of 2.63 is obtained. From this description it can be seen that Fcount (3.052) > Ftable (2.63), and a significance value of 0.029 <0.05, it can be concluded that the fifth hypothesis is accepted